Synthesis and characterization of lithium zeolites with ABW type from coal fly ash. Issue 3 (14th August 2012) - Yao, Zhitong; Ye, Ying; Xia, Meisheng
<x xml:space="preserve">Abstract</x> Lithium zeolites with ABW framework were synthesized from coal fly ash by hydrothermal method. The effects of LiOH·H2O concentrations, hydrothermal temperatures, and reaction time on zeolites formation were investigated. LiOH·H2O acted as a strong activator and promoted the dissolution of coal fly ash. The contents of zeolites ABW phases increased at the expense of quartz and mullite in fly ash with an increase of alkaline solution concentrations. On increasing hydrothermal temperatures and time, the soluble species recrystallized and phase transformation between different zeolites was observed. Morphology evolution revealed that the zeolites developed from radiating cluster to mono‐column. The reaction mechanisms were proposed as well. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 790–796, 2013